Object Color Estimation with Dominant Color in Automated Image Semantic Description Generation Tasks - Poghosyan, Aghasi S. (Mathematical Problems of Computer Science, 2021)
The automated image tagging is an important part of modern search engines. The generated image tags can be constructed from object names and their attributes, for example, colors. This work presents an object color name detection real-time algorithm. It is applicable to any automatic object detection and localization systems. The presented algorithm is fast enough to run after the existing real-time object detection system, without adding visible overhead. The algorithm uses k-means to detect the dominant color and selects the correct name for the color via Delta E (CIE 2000).